1996
DOI: 10.2337/diacare.19.8.843
|View full text |Cite
|
Sign up to set email alerts
|

Potential Therapeutic Levels of Glucagon-Like Peptide I Achieved in Humans by a Buccal Tablet

Abstract: Therapeutic plasma levels of GLP-I in humans were achieved after a single buccal tablet. No increased degradation of GLP-I was found in the buccal mucosa compared to subcutaneous tissue. This alternative treatment form may be feasible in in the future for NIDDM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(61 citation statements)
references
References 24 publications
0
61
0
Order By: Relevance
“…We have shown here that GLP-1 also stimulates the secretion of IAPP in humans. To raise circulating GLP-1, we used a buccal tablet consisting of 400 mg GLP-1, which has been shown to increase plasma GLP-1 levels to approximately 100-150 pmol/l within 30 min (31). These levels of GLP-1 are those required for its antidiabetogenic action (31,32) and, therefore, if GLP-1 were to be used in the treatment of type 2 diabetes, an accompanying increase in circulating IAPP would occur.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have shown here that GLP-1 also stimulates the secretion of IAPP in humans. To raise circulating GLP-1, we used a buccal tablet consisting of 400 mg GLP-1, which has been shown to increase plasma GLP-1 levels to approximately 100-150 pmol/l within 30 min (31). These levels of GLP-1 are those required for its antidiabetogenic action (31,32) and, therefore, if GLP-1 were to be used in the treatment of type 2 diabetes, an accompanying increase in circulating IAPP would occur.…”
Section: Discussionmentioning
confidence: 99%
“…The placebo tablet consisted of the same tablet devoid of GLP-1. The detailed composition of the tablet has been described previously (31).…”
Section: Buccal Tabletmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this experiment were compared with the combined intravenous glucose plus GLP-1 stimulation in the same 8 patients and 7 healthy subjects (in 2 of the 8 patients, a GLP-1 injection without previous administration of glucose was performed instead of a combined glucose plus GLP-1 stimulation because FPG was 15 mmol/l). 10,15,20, 25, 30, 35, 40, 45, 47, 48, 49, 51, 53, 55, 60, 65, 70, 75, and 90 min after elevation of plasma glucose. The L-arginine was dissolved in 50 ml of sterilized water, dispensed into glass ampoules and stored at 4°C until the day of the experiment.…”
mentioning
confidence: 99%
“…It has been reported that GLP-1 administered via buccal tablets 119 nmol or via continuous infusion 2.16 nmol / kg per day for 2 days increases plasma GLP-1 concentrations in humans to a peak of 100−120 pmol / l 26,27 . Therefore, the combined use of DPP-4 inhibitors and GLP-1 could conceivably lead to higher plasma concentrations of GLP-1.…”
Section: Discussionmentioning
confidence: 99%